Transformasi Digital pada Budaya Tradisi Menenun Endek - Nyoman Dewi Pebryani; Tjok Istri Ratna C.S; Anak Agung Rai Remawa; I Made Radiawan (Institut Seni Indonesia Denpasar, 2022)
Endekis traditional textile produce in Bali using a single ikat weaving technique. In single ikat, the resist is formed by binding individual yarns or bundles of yarns with a tight wrapping applied in the desired pattern on one side of threads, either the warpor the weft. Specifically, for Endek, the weft is the threads to form the pattern. Producing patterns in Endekinvolves creativity and intricate calculation; therefore, not many people are able to master this expertise. Transforming the design process of Endekto a digital application provides easiness, as the user only needs to focus on creating the pattern design, while the digital application will calculate the number of threads and visualize the result. To understand the process of creating Endek, the researcher conducted research in the weaving place by interviewing and observing the weavers and pattern makers. The algorithm received from the fieldwork then is translated into programming language to create a digital application. This application is created with a simple user interface so that the user who is not familiar with technology still can practice the apps easily. This application contributes to the efficiency in production process where previously in the production process needs one to two days, while with this application, it can be shortened to one to two hours.